2022
DOI: 10.1093/ptj/pzac056
|View full text |Cite
|
Sign up to set email alerts
|

SAfety and Feasibility of EArly Resistance Training After Median Sternotomy: The SAFE-ARMS Study

Abstract: Objective The purpose of this study was to determine the safety and feasibility of subacute upper limb resistance exercise on sternal micromotion and pain and the reliability of sternal ultrasound assessment following cardiac surgery via median sternotomy. Methods This experimental study used a pretest-posttest design to investigate the effects of upper limb resistance exercise on the sternum in patients following their first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This year's literature focused on a variety of cardiac and pulmonary topics, including early RT after median sternotomy. An experimental study by Pengelly et al 12 in Australia determined the safety and feasibility of subacute upper extremity resistance exercise on pain and sternal micromotion in patients' status postcardiac surgery via median sternotomy. Sternal micromotion was assessed in real-time via sternal ultrasound, and sternal pain was assessed via the visual analog scale, which has been reported as a reliable and valid measure in postoperative patients.…”
Section: Cardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…This year's literature focused on a variety of cardiac and pulmonary topics, including early RT after median sternotomy. An experimental study by Pengelly et al 12 in Australia determined the safety and feasibility of subacute upper extremity resistance exercise on pain and sternal micromotion in patients' status postcardiac surgery via median sternotomy. Sternal micromotion was assessed in real-time via sternal ultrasound, and sternal pain was assessed via the visual analog scale, which has been reported as a reliable and valid measure in postoperative patients.…”
Section: Cardiac Surgerymentioning
confidence: 99%
“…In the literature, it has been hypothesized that greater than 2-mm displacement at the edges of a fracture site may lead to impaired healing and necrosis. 14 The study by Pengelly et al 12 reported that no participant exceeded the 2-mm micromotion threshold during upper-limb exercise and reported no clinical signs or symptoms of sternal complications. The authors concluded that supervised bilateral upper-limb exercises performed on cam-based machines in a controlled environment are safe.…”
Section: Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation